Estimating the economic effects of university-industry collaboration. (2014) - Mark, Michael; Jensen, Rasmus Lund; Norn, Maria Theresa
Universities are widely recognised as important drivers of knowledge-based economic growth, but robust assessments of the short-term, measurable impact of universities on their surrounding environment are few and far between. The present study uses a new and unique dataset on collaborations by the University of Copenhagen to ask the following question: What are the effects on companies' productivity growth of formal collaboration with a research-intensive university? By using Propensity Score Matching to undertake counterfactual analysis and afterwards testing the significance of the results with a difference-in-difference approach, we find evidence of a significant and positive relationship between companies entering into formal R&D collaboration with the university and the subsequent productivity development. We show that the growth patterns of the collaborating companies are significantly stronger compared to those of the selected control group. Implications and questions for further research are discussed.